“Please, mind the gap” : A narrative review on digitalization gaps and barriers in the livestock sector - Stygar, Anna; Niemi, Jarkko K.; Norton, Tomas; Kayhan, Halid; Correa Harcus, Ana Maria; Allain, Clement; Lebreton, Adrien; Anestis, Vasileios; Bartzanas, Thomas; Vouraki, Sotiria; Arsenos, Georgios; Pastell, Matti (Elsevier, 2026)
The livestock sector generates large volumes of data; however, these data remain underutilized. The Data Governance Act, the Data Act of the EU, and recent technological advances, provide an opportunity to automate and improve collection, integration, and use of livestock data. Data spaces, as secure and interoperable environments for data sharing, offer a promising framework to support this transformation. However, this can only be achieved by removing implementation barriers to data sharing and new data generating technologies. The aim of this paper is to provide an overview of key digitalization barriers and gaps in livestock sector. We synthesized existing knowledge across five topics: 1) interoperability, 2) economic viability, 3) technical skills, 4) data privacy and security, and 5) data robustness and quality. Finally, a narrative on how these gaps could be bridged was provided. We argue that bridging these gaps requires a holistic approach combining training, trust building, data governance, and collaboration. EU-level initiatives and projects address some of these areas, but better coordination is needed to maximize impact. The Data Act provides a regulatory foundation for data sharing, yet its limitations, such as its horizontal nature, narrowly defined or unclear terms and exclusion of insights derived from product and related service data, leave critical gaps and may lead to legal disputes. To overcome persistent data lock-in, proactive negotiation, public APIs, and an update on a voluntary industry code of conduct to align with the Data Act are essential for fostering transparency and accelerating adoption of digital solutions.
Keywords: sensors; pigs; dairy; poultry; beef